1973
DOI: 10.4141/cjas73-113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Urea Level on Amino Acid Concentrations in Ruminant Tissues

Abstract: of dietary urea level on amino acid concentrations in ruminant tissues. Can. J. Anim. Sci. 53: 717124.The efiects of a semipurified diet containing0 (0% urea-N diet), diet), or 100% (76% urea-N citrulline, glutamic acid, glycine, and proline were increased. Most of the essential amino acids were decreased on the 76% urea-N diet as compared with the O% urea-N diet. All amino acids of rumen microorganisms were increased on the 397o urea-N diet with the exception of arginine, lysine, and threonine, which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The high concentration of histidine on the uric acid diet was unusual and may be linked to the fact that histidine and uric acid have similar structures. The trend observed in this experiment that the percentage of essential amino acids was higher for diets containing nitrogen rather than non-protein nitrogen has also been reported by Virtanen (1966) in dairy cows, Theurer, Woods & Poley (1968) in lambs and Salem et al (1973) in bulls.…”
Section: Blood Plasma Amino Acids and Ureasupporting
confidence: 86%
See 1 more Smart Citation
“…The high concentration of histidine on the uric acid diet was unusual and may be linked to the fact that histidine and uric acid have similar structures. The trend observed in this experiment that the percentage of essential amino acids was higher for diets containing nitrogen rather than non-protein nitrogen has also been reported by Virtanen (1966) in dairy cows, Theurer, Woods & Poley (1968) in lambs and Salem et al (1973) in bulls.…”
Section: Blood Plasma Amino Acids and Ureasupporting
confidence: 86%
“…It was found that the concentrations of serine, glycine and glutamic acid were higher in the plasma of the calves fed both non-protein nitrogen sources than in the plasma of the calves fed diet C. Similar observations were made in lambs or wethers fed urea or protein supplemented semi-purified diets by Schelling, Hinds & Hatfield (1967) for glycine and serine, Clifford & Tillman (1968) for glutamic acid and aspartic acid and Prior, Milner & Visek (1972) for glycine, serine and glutamic acid. Oltjen & Putnam (1966) found serine and glycine higher and Salem et al (1973) found glycine and glutamic acid to be higher in bulls fed urea supplemented semi-purified diets compared with isolated soyabean protein.…”
Section: Blood Plasma Amino Acids and Ureamentioning
confidence: 99%
“…These values ranged between 3.28 and 3.84 MJ/Kg. Though gas volumes were (64). Regrettably, neither the microbial community profile nor the SCFA fraction including protein utilization were quantified in the current in vitro study, and thus the current results do not provide additional information to speculate on the fate of rumen fermentation.…”
Section: Fermentation Characteristics and Ch 4 Conversion Efficiencymentioning
confidence: 64%
“…Virtanen (1969) eported that cows fed a protein-free diet Lad a lower level of essential amino acids in he plasma than the cows receiving a rrotein-supplemented diet. Salem et al 1973) reported that 240-kg bull calves eceiving 7 kglday of a ration containing '6Vo of the nitrogen as urea nitrogen had ower levels of most essential amino acids han bull calves receiving 7 kgiday of a diet ontaining only soy protein. Similar results vere presented by Ludwick et al (1972) .nd Oltjen and Putnam (1966).…”
Section: Methodsmentioning
confidence: 99%